DETERMINAN RETURN SAHAM SYARIAH DENGAN RISIKO SISTEMATIS SEBAGAI VARIABEL MEDIASI - firmansyah, irman (UNIVERSITY OF MERDEKA MALANG, 2016)
Islamic capital market is the investment alternatives in accordance with Islamic law. However, the purpose of investing is to obtain a high return stock. This study aimed to analyze the fundamental factors in predicting stock return of sharia with systematic risk as a mediating variable. Fundamental factors measured by DER, EPS, ROA, PER and NPM and systematic risk measured by beta. Data taken from the Islamic capital market through the Jakarta Islamic Index (JII) in a span of research in 2013 and 2014. The analysis used is multiple regression analysis and Sobel test. The results showed that DER and PER positive effect on sharia stock return, beta negative effect on sharia stock return and EPS, ROA and NPM no effect on sharia stock return. Whereas in mediating variable testing, the beta did not mediate the relationship between DER, EPS, ROA, NPM and PER to sharia stock return.